Enhancing Auto Strapping Machine Performance Through Six Sigma: A Textile Industry Case Study - Kurnia, Deni; Afzeri; Widiawati, Windi (JURNAL RAMATEKNO, 2025)
In modern industrial manufacturing, production efficiency and quality assurance are critical factors for maintaining competitiveness. One key element in this process is the auto strapping machine, which plays a vital role in packaging and securing products for distribution. However, frequent breakdowns and performance inefficiencies in these machines can disrupt operations, leading to increased downtime and production losses. This study applies the Six Sigma methodology, specifically the DMAIC (Define, Measure, Analyze, Improve, Control) approach, to optimize the performance of auto strapping machines in a textile industry case study. The research identifies major causes of inefficiencies, including mechanical failures, material inconsistencies, and human factors. Using tools such as Pareto charts and Why-Why analysis, the study pinpoints critical failure points, leading to targeted corrective actions such as enhanced maintenance schedules, operator training, and material quality control. The implementation of these improvements resulted in a significant reduction in defects per million opportunities (DPMO) from 794,288 to 517,281 and an improvement in the sigma level from -0.82 to -0.04. These findings highlight the effectiveness of the Six Sigma framework in identifying root causes of machine inefficiencies and implementing structured improvements. The study contributes valuable insights for industries looking to enhance machine reliability and overall operational efficiency. By standardizing best practices and fostering a culture of continuous improvement, manufacturers can reduce downtime, improve product quality, and enhance production sustainability.